Castells - Wetzel, Gereon (Ginestí Rosell, Anna, 2006)
Verzio FF submission Castells are human towers, traditionally built as part of large competitive events in various Catalan communities. These human pyramids are made up of hundreds of people and reach a height of up to ten meters. In fierce competitions the different groups measure their prowess in narrow market-places and demonstrate how perfectly their small communities are holding together. This poetic film follows the fortunes of the Colla Joves team, from the small town of Valls near Tarragona. Driven by their rivalry with the other group from the town, they struggle for victory in the final derby. But their high hopes seem to be endangered by a terrified five-year-old, the tip of the pyramid.